The Evaluation of mental workload using the NASA task load index (NASA-TLX) method on production department employees - Iman, Nurul; Firmansyah, Nunung Agus; Himayati, Ade Ima (Sainteks: Jurnal Sain dan Teknik, 2025)
Human resources are assets and priorities for the company, production activities cannot be carried out optimally and significant losses can occur. From human or employee activities can cause workload, although the level of workload on employees will be different. PT. XYZ is a company engaged in manufacturing the production of bathroom doors from galvanized steel. Production workers often feel the workload, it is complained about by the decline in performance and productivity of work in meeting the company's targets and demands. One of these factors is mental burden that exceeds capacity, thus having an impact on mental health or stress. The purpose of the study was to determine the level of mental workload by measuring and analyzing using the NASA Task Load Index (NASA-TLX) method. The NASA-TLX method is a measurement of mental workload with six indicators, namely Physical Demand, Mental Demand, Temporal Demand, Performance, Effrot, and Frustration. Of the 35 samples of workers in the production unit at PT. XYZ obtained an average score of 85 indicating the "Very High" category with the highest indicators being Effort and Physical Demand. This is influenced by the lack of ergonomic factors of a comfortable and safe work environment system.